AS CHALCONAS NO ENSINO DA QUÍMICA ORGÂNICA EXPERIMENTAL NO CONTEXTO DA QUÍMICA VERDE - Mariana Falcão Lopes P. Carlos; Aurea Echevarria (Química Nova, 2024)
The article presents the importance of practice in teaching Organic Chemistry in higher education, in addition to doing it following the methods of Green Chemistry, in view of how chemistry is seen as a “villain” due to dangerous reactions and incorrect waste disposal toxic. In this work, three chalcones with different substituents were synthesized: an electron donor (OCH3), an electron withdrawer (NO2) and the unsubstituted one, through 4 different methodologies, the first being the traditional methodology (methodology A) and the following methodologies ecofriendly alternatives. Methods B and C through maceration (without solvent), modifying only the support (BaO and Al2O3, respectively) and finally (methodology D) through microwave irradiation. Method C proved to be as efficient as the traditional one, with the advantage of being carried out without solvent and in a shorter reaction time and could be a replacement for the traditional method.